EXPERIENCE OF TEACHING ABOUT THE COMPONENTS OF THE AIR AT THE ELEMENTARY LEVEL - Koul, Anjni (SCHOOL SCIENCE, 2014)
During a field visit, the author decided to go to a rural school in Haryana for a period of three months to transact the concepts given in the science textbooks, developed by NCERT in the light of National Curriculum Framework (NCF-2005). The author wanted to observe whether children are able to comprehend the concepts given in the textbooks, which would have actually given feedback about the textbooks and ultimately would have been helpful in revising these textbooks. In a Government Middle School in Haryana, the author interacted with children of Upper Primary Stage, i.e., Classes VI–VIII. In the present paper the author wants to share one of her experiences while interacting with Class VIII students on the topic16 Components of Air” (NCERT, 2006).